Case Study 3: Effectiveness of Data-Driven Advocacy in Policy Influence in Mauritius - Bundhoo-Deenoo, Sheistah; Vigier de Latour-Bérenger, M. (2024)
The 2024 CHOGM Shadow Report examines the obligations of Commonwealth member states under international human rights law, while taking into consideration the Commonwealth Charter and the 2022 CHOGM Communiqué, in order to provide an overview of the extent to which Commonwealth member states are fulfilling these obligations in the lead-up to CHOGM 2024